SEBARAN KEDALAMAN MUKA AIR TANAH DANGKAL DI SEKITAR PESISIR TELUK KENDARI - Irawati .; Firdaus .; Anda Pou (Jurnal Aplikasi Fisika, 2014)
This study was conducted to determine the potential spread of shallow ground water around the coast of the Gulf of Kendari. Data collection was performed on dug wells located on the gulf coast region of Kendari spread in 5 districts. The research covers in depth the field of geology, ground water level measurement, and the measurement of soil resistivity layer. using geoelectric resistivity method-dc with Schlumberger configuration Furthermore groundwater dispersal patterns mapped using Surfer software 11. Results showed that the distribution pattern of shallow groundwater around the coastal bays are located Kendari at depths between 3.44 m to 9.81 m with resisitivitas value  0.625-3.44 Ωm at which this layer is composed of sand and gravel that contain salt water.